Pengaruh Brand Image, Tagline dan Emotional Branding Terhadap Keputusan Pembelian Sepatu Nike Pada Mahasiswa FEB Unisma - Muslimin, Nurul; Hidayati, Nur; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of Brand Image, Tagline, and Emotional Branding on the purchasing decision of Nike shoes among students of the Faculty of Economics and Business at the Islamic University of Malang. The research population consists of students from the FEB Unisma who use Nike shoes, with a sample of 87 respondents selected using purposive sampling. The data analysis method employed in this study is multiple linear regression. The results show that, Brand Image, Tagline, and Emotional Branding have a positive and significant influence on the purchasing decision of Nike shoes. Keywords: Brand Image, Tagline, Emotional Branding, Purchasing Decision, Nike Shoes